Stiffness of cervical spine after hybrid fusion - Luqman Abdul Halim Lim (2014)
Cervical spondylosis also known as arthritis of the neck, is the degeneration of the joints in the neck. This degenerative disorder is becoming increasingly more common as people age. For patients suffering from such disorders, there are a few options of treatment available such as drug and therapeutic treatment. Surgical treatments are most likely to be considered for patients whose quality of life is significantly affected.